PENGARUH CONSUMER ATTITUDE DAN SUBJECTIVE NORM TERHADAP INTENTION TO BUY SAAT KRISIS MEREK - Gusti Belo Limbong; wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study analyzes the effect of consumer attitude and subjective norm on intention to buy Aqua products amid the water source crisis. Using a quantitative survey of 100 bottled water consumers and multiple linear regression, the results show that consumer attitude positively and significantly affects intention to buy (t = 9.657, sig < 0.001), as does subjective norm (t = 5.606, sig < 0.001). Simultaneously, both variables explain 66.8% of the variance in purchase intention (F = 97.569, R² = 0.668). These findings reinforce the Theory of Reasoned Action (TRA), with consumer attitude proving more dominant than subjective norm in the context of a brand reputation crisis.